Nature through God’s Eyes: Eco-theological Perspectives in Paul Schrader’s First Reformed - Kresentia Madina Jelangdeka; Bayu Kristianto (Journal of Language and Literature, 2021)
Environmental crisis is one of the major issues that humankind is facing today. The crisis can be discussed through a Christian perspective, as the relationship between Christianity and environment has been long discussed for its complexities. Eco-theology is one of the ways for Christianity to bridge its teaching to the environmental crisis. First Reformed, a 2017 film directed by Paul Schrader, is one of the films depicting the interplay between Christianity and environmentalism. This paper examines how First Reformed portrays the process of reconciling Christianity and environmentalism. Using Jürgen Moltmann’s eco-theological concept and Kierkegaard’s concept of despair, this article discovers that while First Reformed demonstrates the ways Christianity could be both an ally and an enemy of environmentalism, the film’s final message leans more towards the way the church can respond to the crisis through embracing insights and values beyond Christianity’s core doctrine that are more in line with environmental concerns, such as seeing nature as a female figure and the idea of harmony illustrated through a yin-yang symbolism.